2010
DOI: 10.1002/nbm.1621
|View full text |Cite
|
Sign up to set email alerts
|

Combined 1H and 31P spectroscopy provides new insights into the pathobiochemistry of brain damage in multiple sclerosis

Abstract: (1)H MRSI has evolved as an important tool to study the onset and progression of brain damage in multiple sclerosis. Abnormal increases in total creatine, total choline and myoinositol have been noted in multiple sclerosis. However, the pathobiochemical mechanisms related to these changes are still largely unclear. The combination of (1)H MRSI and (1)H-decoupled (31)P MRSI can specify to what extent phosphorylated components of total creatine and total choline contribute to this increase. Combined (1)H and (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 53 publications
(45 reference statements)
9
49
0
Order By: Relevance
“…The latter events can be translated as a decrease in PCr levels in MS lesions as previously seen in one study [8] and was also correlated with disease severity in another study [9]. However, in our work, PCr did not correlate with EDSS, which is in line with 2 recent studies [12,13]. This might be due to the fact that our analysis was exclusively performed on NAWM and not MS plaques.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The latter events can be translated as a decrease in PCr levels in MS lesions as previously seen in one study [8] and was also correlated with disease severity in another study [9]. However, in our work, PCr did not correlate with EDSS, which is in line with 2 recent studies [12,13]. This might be due to the fact that our analysis was exclusively performed on NAWM and not MS plaques.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in PCr in NAWM of MS patients is in agreement with previous studies [9,10,11,12,13]. In a normal state, PCr diffuses into astrocytic processes to build up ATP by brain cytosolic creatine kinase isoform (CK-BB), and this transcription is dependent of cyclic adenosine monophosphate (cAMP) [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The MRSI protocol was similar to the one previously described by Hattingen et al [55]. Figure 1 shows the target region at the level of the centrum semiovale including the ACC, which was covered by 2D 1 H MRSI with an axial slice of 12 mm thickness (TR 0 1,500 ms; TE030 ms; two acquisitions).…”
Section: Mr Protocolmentioning
confidence: 99%
“…7 1 H-MR spectroscopy allows noninvasive in vivo measurement of metabolic changes that are able to detect brain damage even in normal-appearing brain tissue. [8][9][10] Cerebral metabolite changes could also be measured by 1 H-MR spectroscopy after SAH, even on morphologically normal MR imaging. 1,7,11,12 Furthermore, Macmillan et al 1 found chronic metabolic changes in patients after aSAH that might be compatible with the neurologic sequelae in patients with SAH.…”
mentioning
confidence: 99%